One-Star Hotel Selection for Staycation using Simple Additive Weighting and Rank Order Centroid - Singgalen, Yerik Afrianto (Universitas Budi Darma, 2024)
The development of the hospitality industry provides many choices to staycation enthusiasts in choosing the right accommodation service. Accommodation service providers also increase competitiveness through excellent service to the addition of facilities to adjust guest preferences and increase sales. The primary objective of this study is to analyze the decision-making behavior associated with choosing one-star hotels for a staycation. The research investigates the decision-making patterns in the context of one-star hotel stays for recreational purposes. The study utilizes the SAW method to evaluate the criteria of facilities, services, rating, cleanliness, value for money, and location, employing Rank Order Centroid (ROC) weighting. In light of the computations using Rank Order Centroid, it is discerned that the weights assigned to the criteria are as follows: W1 with a weight of 0.4083, w2 with a weight of 0.2416, w3 with a weight of 0.1583, w4 with a weight of 0.1027, w5 with a weight of 0.0611, and w6 with a weight of 0.0277. The research findings reveal the aggregation of weighted scores and ranking of alternatives, delineating that A4 attains the first rank with a value of 0.97395, followed by A3, securing the second rank with a value of 0.96511, and A1 acquires the third rank with a value of 0.95191. Thus, the significance of the identified alternative is that it sheds light on its superior performance according to the specified criteria. In conclusion, this research contributes valuable insights into the decision-making dynamics of staycation enthusiasts, pinpointing alternative A4 as the most favorable choice within one-star hotel accommodations.